Motivating film title translation: a cognitive análisis - Peña-Cervel, Mª Sandra (Círculo de Lingüística Aplicada a la Comunicación, 2016)
This proposal is a non-quantitative study based on a corpus of real data which offers a principled account of the translation strategies employed in the translation of English film titles into Spanish in terms of cognitive modeling. More specifically, we draw on Ruiz de Mendoza and Galera’s (2014) work on what they term content (or low-level) cognitive operations, based on either ‘stands for’ or ‘identity’ relations, in order to investigate possible motivating factors for translations which abide by oblique procedures, i.e. for non-literal renderings of source titles. The present proposal is made in consonance with recent findings within the framework of Cognitive Linguistics (Samaniego 2007), which evidence that this linguistic approach can fruitfully address some relevant issues in Translation Studies, the most outstanding for our purposes being the exploration of the cognitive operations which account for the use of translation strategies (Rojo and Ibarretxe-Antuñano 2013: 10), mainly expansion and reduction operations, parameterization, echoing, mitigation and comparison by contrast. This fits in nicely with a descriptive approach to translation and particularly with skopos theory, whose main aim consists in achieving functionally adequate renderings of source texts.